Phase 1 pharmacokinetics and safety study of extended duration dapivirine vaginal rings in the United States. Issue 6 (12th June 2021) - Liu, Albert Y; Dominguez Islas, Clara; Gundacker, Holly; Neradilek, Blazej; Hoesley, Craig; van der Straten, Ariane; Hendrix, Craig W; Beamer, May; Jacobson, Cindy E; McClure, Tara; Harrell, Tanya; Bunge, Katherine; et al.
Abstract: Introduction: Vaginal rings are a promising approach to provide a woman‐centred, long‐acting HIV prevention strategy. Prior trials of a 25 mg dapivirine (DPV) ring have shown a favourable safety profile and approximately 30% risk reduction of HIV‐1 infection. Extended duration rings replaced every three months may encourage user adherence, improve health service efficiency and reduce cost overall. We evaluated safety, pharmacokinetics, adherence and acceptability of two three‐month rings with different DPV dosages, compared with the monthly DPV ring. Methods: From December 2017 to October 2018, MTN‐036/IPM‐047 enrolled 49 HIV‐negative participant in Birmingham, Alabama and San Francisco, California into a phase 1, randomized trial comparing two extended duration (three‐month) rings (100 or 200 mg DPV) to a monthly 25 mg DPV ring, each used over 13 weeks, with follow‐up completed in January 2019. Safety was assessed by recording adverse events (AEs). DPV concentrations were quantified in plasma, cervicovaginal fluid (CVF) and cervical tissue, at nominal timepoints. Geometric mean ratios (GMRs) relative to the comparator ring were estimated from a regression model. Results: There were no differences in the proportion of participants with grade ≥2 genitourinary AEs or grade ≥3 AEs in the extended duration versus monthly ring arms ( p = 1.0). Plasma and CVF DPV concentrations were higher in the extended duration rings compared to the monthly ring. Plasma GMRs were 1.31 to 1.85 and 1.41 to 1.86 and CVF GMRs were 1.45 to 2.87 and 1.74 to 2.60 for the 100 and 200 mg ring respectively. Cervical tissue concentrations were consistently higher in the 200 mg ring (GMRs 2.36 to 3.97). The majority of participants (82%) were fully adherent (ring inserted at all times, with no product discontinuations/outages) with no differences between the monthly versus three‐month rings. Most participants found the ring acceptable (median = 8 on 10‐point Likert scale), with a greater proportion of participants reporting high acceptability (9 or 10) in the 25 mg arm (73%) compared with the 100 mg (25%) and 200 mg (44%) arms ( p = 0.01 and p = 0.15 respectively). Conclusions: The extended duration DPV rings were well‐tolerated and achieved higher DPV concentrations compared with the monthly DPV ring. These findings support further evaluation of three‐month DPV rings for HIV prevention.